TOPONYMY OF VILLAGES IN KENDARI CITY BASED ON HISTORICAL ASPECTS AND EVENTS: ANTHROPOLINGUISTIC STUDY - Nurwulan, Zulhilda; Sulistyowati (Prologue: Journal on Language and Literature, 2024)
This qualitative research with an anthropolinguistic approach aims to determine the linguistic form of the names of sub-districts in Kendari City and to find out the meaning of the names of sub-districts in Kendari City based on historical aspects and events. This research is motivated by the lack of language literature related to Kendari City, especially in the field of toponymy, so that there are still many people who do not familiar w the names of sub-districts in Kendari City. The data in this research are 25 sub-districts from five sub-districts in Kendari City which were chosen randomly. Data collection was carried out by means of literature studies and interviews with three sources who aware about the history of Kendari City. The results show the toponymic language forms of sub-districts in Kendari City are in the form of single words, complex words and phrases. Regarding the meaning of toponymy, villages in Kendari City are dominated by history. The research results can be used as reference material for further research on similar topics so that the results vary.